2019
DOI: 10.32861/jac.59.158.161
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Rain-Fed Wheat Production Constraints in Zambia

Abstract: Wheat (Triticum aestivum L.) is an important food crop in Zambia. It is the second most widely grown cereal crop after maize. However, its production and productivity during summer rain season is limited by socio-economic, abiotic and biotic constraints. The socio-economic factors limiting high wheat yield are high cost of inputs, lack of improved rain-fed wheat seed, lack of affordable loans, lack of access to market information and poor mechanization. The abiotic constraints on the other hand include drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…After correcting those conditions, the specificity of the MoT3 was reconfirmed using the same strains (Yasuhara-Bell et al 2019). Moreover, the loss of the MoT3 allele may be possible due to hybridization events through inter-lineages recombination, which may explain the small failure rate, according to the authors (Pieck et al 2017;Yasuhara-Bell et al 2018a, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After correcting those conditions, the specificity of the MoT3 was reconfirmed using the same strains (Yasuhara-Bell et al 2019). Moreover, the loss of the MoT3 allele may be possible due to hybridization events through inter-lineages recombination, which may explain the small failure rate, according to the authors (Pieck et al 2017;Yasuhara-Bell et al 2018a, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Even being one of Bangladesh's neighbor countries and having conductive weather conditions to wheat blast occurrence, no formal scientific reports confirmed the wheat blast introduction in India (Islam et al 2020, Singh et al 2021. More recently, the wheat blast pathogen arrived in Africa: Zambia (Tembo 2019;Tembo et al 2020) (Figure 1). (Viedma 2005;Pieck et al 2017), Uruguay (Saharan et al 2016;Yasuhara-Bell et al 2018b), Argentina (Perelló et al 2015), United States (Farman et al 2017), Bangladesh (Islam et al 2016), and Zambia (Tembo et al 2020(Tembo et al , 2021Croll 2021).…”
Section: Geographical Distribution Of Wheat Blastmentioning
confidence: 99%
See 1 more Smart Citation
“…There are current efforts by the Zambia Agriculture Research Institute (ZARI) to promote rain-fed growing of wheat among smallholder farmers in Zambia. The positive impact of such efforts in Zambia will be reduced by the emergency of wheat blast disease coupled with other fungal diseases that have been reported in Zambia [16]. It is therefore important that measures to limit damage to wheat crops be instituted and collaborative research efforts started to prevent spread of the disease to new areas.…”
Section: Discussionmentioning
confidence: 99%
“…Rain-fed wheat yields are not only low, they also fluctuate considerably. Their fluctuation can be attributed to different stresses, such as heat, drought, rainfall, soils, and diseases, and/or lack of improved and adaptable varieties (Tembo, 2019). Yan and Kang (2003) reported that the performance of a genotype in an environment is a function of genotype, environment, and genotype by environment interaction (GEI).…”
Section: Introductionmentioning
confidence: 99%